2017
DOI: 10.1186/s40793-017-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Russian wheat aphid an economically important cereal aphid

Abstract: Although the hemipterans (Aphididae) are comprised of roughly 50,000 extant insect species, only four have sequenced genomes that are publically available, namely Acyrthosiphon pisum (pea aphid), Rhodnius prolixus (Kissing bug), Myzus persicae (Green peach aphid) and Diuraphis noxia (Russian wheat aphid). As a significant proportion of agricultural pests are phloem feeding aphids, it is crucial for sustained global food security that a greater understanding of the genomic and molecular functioning of this fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
(59 reference statements)
2
19
0
Order By: Relevance
“…Here we report the genome sequence of R. maidis isolate BTI-1. Comparisons to six previously published aphid genomes [24][25][26][27][28][29][30][31] showed an improved assembly, with most of the sequences assembled into four scaffolds, consistent with the 2n = 8 karyotype of R. maidis.…”
Section: Data Description Introductionsupporting
confidence: 70%
“…Here we report the genome sequence of R. maidis isolate BTI-1. Comparisons to six previously published aphid genomes [24][25][26][27][28][29][30][31] showed an improved assembly, with most of the sequences assembled into four scaffolds, consistent with the 2n = 8 karyotype of R. maidis.…”
Section: Data Description Introductionsupporting
confidence: 70%
“…For instance, Diuraphis noxia (Russian wheat aphid) was first detected in Australia in 2016, and successful control of this species now depends, in part, on identifying past and present sources of incursions (Yazdani et al, 2018). Although a recent genome assembly of D. noxia suggests that this species has low genetic variability (Burger & Botha, 2017), genome-wide SNPs may yet provide sufficient power to determine broad patterns of gene flow. Likewise, similar methodologies may help untangle the complexity of marine invasion narratives, in which many processes remain cryptic when analysed without the appropriate molecular tools (Ojaveer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the cellular component category, contribution of different components was similarly shared between protein complex (30%), nuclease (25%), cytoplasmic part (24%) and intracellular non-membrane bound organelles (21%). This is in stark contrast to that of the rest of the genome, where the largest components comprised of general function and signal transduction (Burger & Botha 2017). The distribution of enzyme codes derived from the PCGs suggested that hydrolases were the largest contributor to enzyme function on X chromosome, representing more than 50% of the total EC classes in the analysis (Fig.…”
Section: Next-generation Sequencing and Assemblymentioning
confidence: 92%
“…These poor quality reads were filtered and trimmed by making use of FASTX-Toolkit (http://hannonlab.cshl.edu/fastx_ toolkit/) to ensure that for a pair of paired-end reads each dataset had 90% or more bases with a phred score greater than or equal to Q20. Quality trimmed reads were aligned to the Russian wheat aphid (RWA) reference genome (SAM_Contigs_Version 1.1; GCA_0014 65515.1, Burger & Botha 2017;and GCA_0011 86385.1, Nicholson et al 2015) as well as to that of the pea aphid (Acyr_2.0; GCA_000142985.2, The International Aphid Genomics Consortium 2010) using the Burrows-Wheeler aligner with default parameters (Li & Durbin 2010). The quality of the alignments was assessed by using Qualimap (García-Alcalde et al 2012).…”
Section: Dna Extraction and Ngsmentioning
confidence: 99%
See 1 more Smart Citation